2011
DOI: 10.1177/1468087411422846
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental studies of air-hybrid engine operation with fully variable valve actuation

Abstract: As an alternative to the electric hybrid powertrain, air-hybrid engine concepts have the potential to achieve regenerative braking and air-assisted engine operations for low-carbon vehicle applications. Over the last few years, systematic studies have been carried out by the authors on a number of air-hybrid engine concepts. This paper presents the modelling and experimental results of air-hybrid engine operation enabled by fully variable valve actuation (FVVA). The principle and key operating features of such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…As part of the initial investigation on performance and potential of the air hybrid engine, experimental studies were carried out in a single-cylinder research engine with the Lotus’ fully variable valve actuation (FVVA) system in the authors’ laboratory. 1,2 The experimental study and the engine modelling results demonstrated the capability of the FVVA system to enable air hybrid operation for internal combustion engines. It was shown that the two-stroke compressor mode and expander mode operations were the most effective air hybrid operations and could be readily achieved with the FVVA system together with a dedicated compressed air transfer passage in the cylinder head.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…As part of the initial investigation on performance and potential of the air hybrid engine, experimental studies were carried out in a single-cylinder research engine with the Lotus’ fully variable valve actuation (FVVA) system in the authors’ laboratory. 1,2 The experimental study and the engine modelling results demonstrated the capability of the FVVA system to enable air hybrid operation for internal combustion engines. It was shown that the two-stroke compressor mode and expander mode operations were the most effective air hybrid operations and could be readily achieved with the FVVA system together with a dedicated compressed air transfer passage in the cylinder head.…”
Section: Introductionmentioning
confidence: 90%
“…As part of the initial investigation on performance and potential of the air hybrid engine, experimental studies were carried out in a single cylinder research engine with the Lotus' fully variable valve actuation system (FVVA) in the authors laboratory [1][2]. The experimental study as well as the engine modelling results demonstrated the capability of the FVVA system to enable air-hybrid operation for internal combustion engines.…”
Section: Introductionmentioning
confidence: 99%
“…The fuel saving was up to 35%, compared with that of a naturally aspirated spark ignition engine with the same rated power. Zhao et al 17 and Turner et al 18 have also conducted pneumatic hybrid research by adopting electrohydraulic valve systems on all valves.…”
Section: Introductionmentioning
confidence: 99%
“…Psanis 13 and Zhao et al 14 have also tested the full air hybrid operation on a single cylinder research engine with a Lotus fully variable valve actuation system (FVVA). 13,14 According to the modelling and experimental results, two-stroke compressor mode (CM) and expander mode operations can achieve most effective air hybrid operations.…”
Section: Introductionmentioning
confidence: 99%